Impact of a supported housing prioritization system using vulnerability and high service utilization. Issue 2 (3rd July 2017) - Srebnik, D.; Sylla, L.; Hoffman, M.; Franzen, R.
ABSTRACT: For people experiencing chronic homelessness, supportive housing with intensive social, health, and behavioral health services reduces the likelihood of re-entering homelessness and the public costs of associated acute medical care, shelter use, and incarceration. Due to a limited supply of supportive housing, it must be allocated to those most in need. This paper examines findings from a unique, region-wide method for prioritizing individuals for supportive housing based on utilization of high-cost public services and vulnerability if left on the street. A sample of 196 individuals were prioritized for housing based on this method, while a comparison group of 102 were housed not using the method. Results showed that those housed under the prioritization method achieved greater reductions in utilization of high-cost public services, but were also less likely to have positive dispositions when exiting the housing programs, suggesting the need for a greater intensity of supports and/or multiple "doses" of supportive housing before stability can be expected. The method described in the paper can provide a starting point for developing regional, comprehensive systems of coordinated, prioritized entry into supportive housing, such as those now required by US Department of Housing and Urban Development.